Knowledge and Anxiety Related to Hereditary Ovarian Cancer in Serous Ovarian Cancer Patients - Sang Hee Lee; Hyangkyu Lee; Myong Cheol Lim; Sue Kim (Korean Journal of Women Health Nursing, 2019)
PURPOSE: The awareness of hereditary breast and ovarian cancer (HBOC) and BRCA testing is increasing in Korea. Compared to the sizable research on HBOC knowledge among breast cancer women, studies in the ovarian cancer population are limited. This paper aimed to investigate the level of knowledge of hereditary ovarian cancer and anxiety in women diagnosed with serous ovarian cancer in Korea and determine differences in the knowledge and anxiety according to whether genetic testing was undertaken and whether BRCA1 or BRCA2 mutations were present. METHODS: Using a descriptive research design, a cross-sectional survey was conducted on 100 women diagnosed with serous ovarian cancer at N hospital in Gyeonggi-do, Korea, from July to November 2018. The collected data were analyzed by descriptive statistics, independent t-tests, one-way analysis of variance, and Pearson's correlation coefficient using the SPSS 21.0 program. RESULTS: The hereditary ovarian cancer-related knowledge score was mid-level (mean score 8.90±3.29 out of a total of 17), as was the state anxiety level was mid-level (mean score 47.96±3.26 out of possible score range of 20–80). Genetic knowledge of hereditary ovarian cancer was associated with age, education, occupation, genetic counseling, and BRCA mutations. There were no statistically significant factors related to anxiety and there were no statistically significant correlations between knowledge level and anxiety. CONCLUSION: More comprehensive education on gene-related cancer is needed for ovarian cancer patients, especially for items with low knowledge scores. A genetic counseling protocol should be developed to allow more patients to alleviate their anxiety through genetic counseling.